Alignment of liquid crystals by polymers with residual amounts of solvents - Alexander M. Parshin (Nature Portfolio, 2017)
Abstract The homogeneous nematic layers in liquid crystal cells with treated surfaces are affected by orientational transitions in the electric, magnetic, or temperature fields. The liquid crystal structures formed on solid or liquid surfaces find limited application in identifying the liquid-crystal states by the textures observed in polarized light. The use of surfaces prepared from polymer solutions makes it possible to significantly broaden the range of application of the liquid crystal structures. We investigate the structures with the continuous transformation of the nematic director orientation from radial to planar, which were formed by the polycarbonate surface in the presence of different residual solvents. The structures contained the disclination lines that aligned either by a plate rubbed to provide the homogeneous planar orientation in the LC layer or by a magnetic field applied along the polycarbonate film during the structure formation. The orientational transitions caused by surface treatment, temperature, and electric or magnetic fields in these structures are observed. The comparison of temperature critical distance as well as electric and magnetic coherence lengths with equilibrium length calculated from the expression for the free energy of the nematic is performed. The electro-optical characteristics of the nematic structures are obtained.